Longitudinal associations between cognitive ability and socioeconomic status are partially genetic in nature - Kajonius, Petri J. (Scientific Reports, 2026)
Individual’s future socioeconomic status (SES) has been reported to be robustly predicted by cognitive ability (IQ). However, research on the genetic and environmental underpinnings of this association in emerging adults remains limited. Utilizing the German TwinLife panel data, the present study examined how IQ at early adulthood at age 23 is associated with SES at age 27 (NMZ = 228 and NDZ−SAME SEX = 212), through 2 measures on educational attainment and 2 on occupational status. Cholesky decomposition models reported the heritability of IQ at approximately 75%, and heritability on all SES outcomes. Genetic factors further explained most of the IQ–SES association (69–98%), and genetic correlations between IQ and SES exceeded environmental correlations. These findings seem to underscore the importance of researchers and policymakers to also considering genetic factors when examining the life outcomes of young adults.
Keywords: Cognitive ability; Intelligence; IQ; SES; Socioeconomic status; Twins